2021
DOI: 10.1016/j.crad.2020.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of chest radiograph interpretation for pulmonary tuberculosis in the screening of childhood TB contacts and migrant children in the UK

Abstract: To determine interobserver agreement between paediatric radiologists interpreting tuberculosis (TB) screening chest radiographs (CXR) in children in the UK, and the TB detection rate.MATERIALS AND METHODS: A retrospective review was undertaken of electronic request, notes, and CXRs (>7 years) in children exposed to an infectious case of TB and new entrants to the UK, at a tertiary children's hospital. Included were those with positive Mantoux/interferon gamma release assay (IGRA), positive culture, or high cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…In 2021 Khuawar et al, while studying Tuberculosis as a forecaster of childhood malnutrition in Sindh, Pakistan observed that 13% children infected with TB were found with low BMI and low nutrition marker [26]. In our study almost all physicians reported asking for X-ray chest for diagnosis of pulmonary TB.In contrast, in 2020 a study conducted by Andronikou et al, in UK suggests the routine practice for chest X-ray is disputed because of only moderate reliability [27]. In our study majority physicians prescribed investigations including complete blood count (CBC) and erythrocyte sedimentation rate (ESR).…”
Section: Discussionmentioning
confidence: 52%
“…In 2021 Khuawar et al, while studying Tuberculosis as a forecaster of childhood malnutrition in Sindh, Pakistan observed that 13% children infected with TB were found with low BMI and low nutrition marker [26]. In our study almost all physicians reported asking for X-ray chest for diagnosis of pulmonary TB.In contrast, in 2020 a study conducted by Andronikou et al, in UK suggests the routine practice for chest X-ray is disputed because of only moderate reliability [27]. In our study majority physicians prescribed investigations including complete blood count (CBC) and erythrocyte sedimentation rate (ESR).…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, Berteloot et al [28] reported a kappa value of 0.36 between radiologist and pediatric pulmonologist. Lastly, Andronikou et al [29] presented a kappa value of 0.5 between trained pediatric radiologists, although their dataset included older children with a mean age of 9 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of developing TB is low in most developed countries, the risk of infection increases with age [28]. There is an estimated likelihood that one in twenty-five people will develop active TB during their lifetimes in the United States [29]. There are approximately 140 cases of tuberculosis per 100,000 people in South Africa every year, making it one of the highest rates in the world [30].…”
Section: Prevalence Of Tbmentioning
confidence: 99%